Tumor Burden Measured by 18F-FDG PET/CT in Predicting Efficacy and Adverse Effects of Chimeric Antigen Receptor T-Cell Therapy in Non-Hodgkin Lymphoma - Hong, Ruimin; Tan Su Yin, Elaine; Wang, Linqin; Zhao, Xin; Zhou, Linghui; Wang, Guangfa; Zhang, Mingming; Zhao, Houli; Wei, Guoqing; Wang, Yiyun; Wu, Wenjun; Zhang, Yafei; et al. (Frontiers in Oncology, 2021)
Chimeric antigen receptor (CAR) T cell therapy has exhibited promising clinical outcomes in treating relapsed/refractory (R/R) B-cell hematologic malignancies. Current studies have shown a close correlation between baseline tumor burden and therapeutic response in CAR-T cell therapy. However, the roles of PET/CT metabolic parameters, such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG), remain unclear in this setting. In this study, we retrospectively reviewed 41 R/R NHL patients. 18F-FDG PET/CT was used to measure the average standardized uptake value (SUVavg), MTV, and TLG of the lymphomatous lesions. These patients were divided into two groups according to the optimal cutoff values of respective PET/CT metabolic parameters. The multivariate analysis depicted that early post-therapy SUVavg (HR: 1.418, 95%CI: 1.029, 1.955; P=0.033) and MTV (HR: 1.001, 95%CI: 1.000, 1.002; P=0.041) were independent risk factors associated with OS and PFS, respectively. Patients with baseline SUVavg＜4.36 achieved a superior 1-year OS rate than SUVavg≥4.36 group (100.0% vs. 44.9%, P=0.019). For the patients with lower values in early post-therapy SUVavg (＜2.60) (51.1% vs. 0%, P＜0.001), MTV(＜0.55cm3) (53.6% vs. 0.0 %, P=0.001), and TLG (＜1.54) (53.6% vs. 0.0 %, P=0.001), their 1-year PFS rates were higher than the compared groups. Moreover, patients with higher baseline tumor burdens were found to have significantly increased CRS incidence and cytokine levels. In conclusion, The PET-CT metabolic parameters are closely related to OS, PFS, and CRS in R/R NHL patients treated with CAR-T cells. This study may pave the way for building a comprehensive assessment system of tumor burden using 18F-FDG PET/CT, which can optimize therapeutic and supportive approaches in CAR-T cell therapy.